Associations between neutrophil-percentage-to-albumin ratio level and all-cause mortality and cardiovascular disease-cause mortality in general population: evidence from NHANES 1999–2010 - Liu, Yuting; Qiu, Zifeng; Shen, Geng; Sun, YangYang; Mei, Jiarong; Liu, Zhihao; Wang, Leyi; Li, Jianping (Frontiers in Cardiovascular Medicine, 2024)
Introduction Chronic inflammation is a recognized independent risk factor for cardiovascular disease (CVD), highlighting the need for reliable inflammatory indicator to predict CVDs. As an inflammatory indicator which has been proved to have predictive value for prognosis of CVDs, neutrophil percentage-to-albumin ratio (NPAR) has obtained increasing attention, but further research is needed to confirm the relationship with mortality in the general population. Method This prospective cohort study included 21,317 individuals who participated in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2010, where baseline characteristics and NPAR level were extracted. Data for CVD and all-cause mortality were acquired by linking the cohort database with the National Death Index through December 31, 2019. We employed restricted cubic spline analyses to examine the nonlinear association. Weighted Kaplan–Meier curves with log-rank tests were conducted to access cumulative survival differences across different NPAR results. Multivariable Cox proportional hazards regression models were used to compute hazard ratios and 95% CIs. Receiver Operating Characteristic (ROC) curves were used to compare predictive value of NPAR with systemic immune inflammation index (SII) and neutrophils percent. Results In this cohort study, during 270,014 person-years of follow-up, 4,074 all-cause deaths and 1,116 CVD-cause deaths were documented. NPAR levels exhibited significant nonlinear associations with both CVD-cause (P = 0.018 for nonlinearity) and all-cause mortality (P < 0.001 for nonlinearity). Participants in the highest NPAR tertile had a significantly increased risk of all-cause mortality (HR: 1.46, 95% CI: 1.33–1.61) and CVD-cause mortality (HR: 1.54, 95% CI: 1.32–1.80) compared to those in the lowest tertile in the fully adjusted model, while no association was detected for individuals in the middle tertile. Further ROC analysis confirmed that NPAR had higher predictive value than neutrophil percent segment and SII. Conclusions Elevated NPAR level was significantly associated with an increased risk of all-cause and CVD-cause mortality in general population. The high predictive value of NPAR, combined with the easy-to-calculate property, suggests that its potential as a novel inflammatory indicator is worthy of further investigation.